DIGITALIZATION OF CREATIVE INDUSTRIES IN CULTURE AND AWARENESS IN THE MINDS OF WICKS OF MINISTRAL SUSPENDSHIP - Любарець, Владислава; Кривец, Юрій (SWorldJournal, 2024)
The article emphasizes the importance and peculiarities of digitalization of creative industries in culture and education in the context of the challenges of a changing society as a priority direction of research into the development of scientific-technic